2020
DOI: 10.1086/706305
|View full text |Cite
|
Sign up to set email alerts
|

Gliding Dragons and Flying Squirrels: Diversifying versus Stabilizing Selection on Morphology following the Evolution of an Innovation

Abstract: Evolutionary innovations and ecological competition are factors often cited as drivers of adaptive diversification. Yet many innovations result in stabilizing rather than diversifying selection on morphology, and morphological disparity among coexisting species can reflect competitive exclusion (species sorting) rather than sympatric adaptive divergence (character displacement). We studied the innovation of gliding in dragons (Agamidae) and squirrels (Sciuridae) and its effect on subsequent body size diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…In contrast, BM models exclude an attractor parameter, and thus the strong fit of BM1m.All (and poor fits of OUM models) indicates a lack of selective pressures for a specific glider skeletal morphology. Consistent with this observation, Ord et al (2020) found no evidence of stabilizing selection (via a lack of support for OU models) on the morphology of flying squirrels (Pteromyini), and flying squirrels in our sample occupy a substantial region of phylomorphospace (Figs. 3A and 3B).…”
Section: Model-fitting Analysessupporting
confidence: 84%
“…In contrast, BM models exclude an attractor parameter, and thus the strong fit of BM1m.All (and poor fits of OUM models) indicates a lack of selective pressures for a specific glider skeletal morphology. Consistent with this observation, Ord et al (2020) found no evidence of stabilizing selection (via a lack of support for OU models) on the morphology of flying squirrels (Pteromyini), and flying squirrels in our sample occupy a substantial region of phylomorphospace (Figs. 3A and 3B).…”
Section: Model-fitting Analysessupporting
confidence: 84%
“…Those based on within‐taxon intercept values were necessarily restricted to those taxa included in the contextual reaction norm analyses. The phylogeny of Draco was taken from Ord et al (2020), with populations within taxa inferred assuming the minimum intra‐island population divergence reported for Philippine Draco by McGuire and Heang (2001). For Anolis , one species ( Anolis poncensis ) had a vastly reduced dewlap to the extent that it was functionally absent from the display (Ord et al, 2013a) and was not included in analyses of the dewlap display.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike other agamid groups, Draco is a remarkable ecological analogue to the Anolis . Although there are obvious differences between the two groups— Draco is the only group to have evolved the ability to glide (Ord et al, 2020)— Draco and Anolis lizards are both arboreal, share key morphological adaptations to common structural environments (convergent limb lengths as a function of perch circumference as well as other aspects of ecomorphology; Ord & Klomp, 2014) and employ remarkably similar movements in their territorial displays (Mori & Hikida, 1994). In particular, both Draco and Anolis have independently evolved a large, conspicuous dewlap (Ord et al, 2015) that is extended and retracted as part of a main territorial display.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance placed on concepts like ecological opportunity (or release) in how diversification is instigated (Yoder et al 2010;Stroud & Losos 2016), and given these clearly rely on taxa making transitions in habitat in the first instance, investigating both the cause and consequence of invasion is vital for not only understanding why some taxa are better invaders than others (e.g., generalists versus specialists), but also what circumstances facilitate those transitions that go on to promote (or even constrain: e.g., Ord et al 2019) diversification in some groups but not others (innovations or plasticity). In this study we examined how diet and behavioural plasticity have contributed to habitat transitions in a diverse fish group and how adaptive evolution has proceeded in key aspects of trophic morphology following these transitions.…”
Section: Introductionmentioning
confidence: 99%